2010
DOI: 10.1111/j.1872-034x.2010.00643.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of spleen volume is useful for distinguishing between simple steatosis and early‐stage non‐alcoholic steatohepatitis

Abstract: Spleen enlargement may be a distinct feature of NASH, especially early-stage NASH. SBI might be a non-invasive and simple method of differentiating NASH and simple steatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 31 publications
5
20
0
1
Order By: Relevance
“…Data of previous studies suggest that clues of AST aspartate aminotransferase, ALT alanine aminotransferase * Student T test steatohepatitis in NAFLD patients can be an increase in portal vein diameter, reduction of portal vein velocity, large splenic area, and an increase in RI of splenic artery [10,15,16]. In our baseline, similar characteristics were found in NAFLD patients with severe fatty liver disease (Table 2).…”
Section: Discussionsupporting
confidence: 81%
“…Data of previous studies suggest that clues of AST aspartate aminotransferase, ALT alanine aminotransferase * Student T test steatohepatitis in NAFLD patients can be an increase in portal vein diameter, reduction of portal vein velocity, large splenic area, and an increase in RI of splenic artery [10,15,16]. In our baseline, similar characteristics were found in NAFLD patients with severe fatty liver disease (Table 2).…”
Section: Discussionsupporting
confidence: 81%
“…In the current study a statistically highly significant positive correlation existedbetween the degree of steatosis and size of the spleen. This was in agreement with Suzukiet al, who found larger splenic size in patients with simple steatosis and NASH (16) . There are reports which had suggested that enlarged hepatocytes arising from steatosiscompress the sinusoids and lead to portal hypertension in NASH patients (17) .…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, Mendes et alperformed a study on patients of NASH with no fibrosis and found that (6%) of patientswith steatosis had portal hypertension (5) . It is of notice that changes in liver blood flow in steatosis partly resemble thoseseen in cirrhosis, in which the intra-hepatic portal flow is usually reduced attributed to anincreased intrahepatic vascular resistance resulting in increase in the portal pressure (16) . In the current study a statistically highly significant positive correlation existedbetween the degree of steatosis and size of the spleen.…”
Section: Discussionmentioning
confidence: 99%
“…In NASH (as occurs with alcoholic liver disease), fibrosis begins around the central veins; therefore, the symptoms of portal hypertension are thought to appear first as a result of central vein occlusion [28,29]. The spleen volume is speculated to increase as the portal blood pressure increases in chronic liver disease [30], and we previously reported that splenic enlargement may be a distinct feature of NASH [31].…”
Section: Discussionmentioning
confidence: 97%